On new ?2-convergent difference BK-spaces - Ercan, Sinan; Bektas, Cigdem A. (Eudoxus Press, Llc, 2017)
In this paper, we introduce the spaces c(lambda(2), Delta) and c(0)(lambda(2), Delta), which are BK-spaces of non-absolute type and we prove that these spaces are linearly isomorphic to the spaces c and c(0), respectively. Moreover, we give some inclusion relations and compute the alpha-, beta- and gamma-duals of these spaces. We also determine the Schauder basis of the c(lambda(2), Delta) and c(0)(lambda(2), Delta). Lastly we give some matrix transformations between of these spaces and others.
Keywords: lambda(2)-convergence; BK-spaces; alpha-, beta- and gamma- duals; matrix mappings; difference sequence; spaces